Somalia: State Collapse, Terrorism and Piracy - Vilas-Bôas, Júlia Covre (Meridiano 47 - Journal of Global Studies, 2017)
HESSE, Brian. Somalia: State Collapse, Terrorism and Piracy. Londres e Nova York: Routledge: Taylor & Francis Group, 2011 (ISBN 0415594634).